A study of mechanical properties of bone cement containing micro- and nano- hydroxyapatite particles - Phanrawee Sriprapha (2018)
© 2018 Trans Tech Publications, Switzerland. In this research, mechanical properties of bone cement containing micro- and nano-hydroxyapatite (HAp) particles were studied. The bone cement was prepared from mixing between polymethyl methacrylate (PMMA) and methyl methacrylate (MMA). Hydroxyapatite powder was prepared from bovine bone. The bone was heated in hot water at 200oc for the elimination of tissue, after which the bone was dried and calcined at 800oc for 3 hrs. The calcined bone then was crushed into powder and ball-milled for 24 hrs. The micro-HAp particle was then obtained. The micro particles were then further milled employing the Vibro-milling machine for 2 hrs. The micro- and nano- HAp sizes are about 0.5 µm and 140 nm, respectively. The both size powders were treated with γ-methacrylic-propyl-tri-methoxy silane. The acetic acid was added to control the pH of the solution, until it reached 2.9 before they were mixed into the bone cement with equally wt%. The mixture was casted using the 304 stainless steel mold in order to obtain a cylindrical shape. The low vacuum scanning electron microscope (LV-SEM) and x-ray diffractometer (XRD) were employed to characterize the samples. The porosity of PMMA could be reduced by HAp particle additives. From compressive strength test, it was found that the mixture of bone cement and nano-HAp particle has shown higher compressive strength than pure PMMA bone cement that affected by porosity reduction and force distribution by HAp particles.